2020
DOI: 10.1016/j.eucr.2019.101028
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral wunderlich syndrome secondary to synchronous bilateral testicular germ cell tumor. A case report

Abstract: Testicular cancer accounts for 1% of male neoplasms, the most common histology is bilateral presentation is reported in 1–2% of cases, and germ cell tumor histology represents 90–95% of cases. Especifically, choriocarcinoma as a pure component represents 0.3–1% of these neoplasms and as a mixed component, 8%. We present a 26-year-old male patient with bilateral Wunderlich syndrome secondary to renal metastases from testicular choriocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…A month later, the first patient, after completing 2 cycles of chemotherapy with objective clinical, biochemical, and imaging improvement in all metastatic lesions (thorax, retroperitoneum), suffered from an episode of massive hematochezia and died [18] . Pure choriocarcinoma has an aggressive oncological behavior with high metastatic capacity such as choriocarcinoma syndrome which causes bleeding in metastatic sites and significant morbidity and mortality 3; Alvarado/Hernandez et al reported a series of 15 patients with choriocarcinoma as a pure or predominant component, finding 100 % of cases with metastases (pulmonary 66 %, hepatic 60 %, brain 20 % gastrointestinal tract 13 % and renal 6 %) 4; There are few studies or reports in the literature of retroperitoneal bleeding or better known as Wunderlich syndrome in association with testicular cancer, finding publications such as Yee-Huang Ku et al, in 2018 reporting a case of spontaneous retroperitoneal bleeding secondary to testicular choriocarcinoma, 3 or as published by Huang et al reporting another case of choriocarcinoma-type testicular carcinoma with metastatic retroperitoneal involvement associated with Wunderlich syndrome 5; In Salgado et al case, the high aggressiveness of this type of testicular tumors is clearly evidenced, documenting metastasis to the kidney and mesentery, confirming with the histopathological result the commitment to choriocarcinoma, patient was treated in intensive care unit for hemorrhagic shock grade IV, acute liver failure and acute renal failure, presenting poor evolution with subsequent death at 24 h [19] . Venkata et al also presented a 23 year old male with increasing abdominal pain, diarrhea, episodic vomiting for 3 weeks, the CT scan of the abdomen revealed a caecal mass with multiple metastases to liver, lungs and abdominal lymph nodes and biopsies from the mass were reported as poorly differentiated metastatic carcinoma.…”
Section: Clinical Discussionmentioning
confidence: 74%
“…A month later, the first patient, after completing 2 cycles of chemotherapy with objective clinical, biochemical, and imaging improvement in all metastatic lesions (thorax, retroperitoneum), suffered from an episode of massive hematochezia and died [18] . Pure choriocarcinoma has an aggressive oncological behavior with high metastatic capacity such as choriocarcinoma syndrome which causes bleeding in metastatic sites and significant morbidity and mortality 3; Alvarado/Hernandez et al reported a series of 15 patients with choriocarcinoma as a pure or predominant component, finding 100 % of cases with metastases (pulmonary 66 %, hepatic 60 %, brain 20 % gastrointestinal tract 13 % and renal 6 %) 4; There are few studies or reports in the literature of retroperitoneal bleeding or better known as Wunderlich syndrome in association with testicular cancer, finding publications such as Yee-Huang Ku et al, in 2018 reporting a case of spontaneous retroperitoneal bleeding secondary to testicular choriocarcinoma, 3 or as published by Huang et al reporting another case of choriocarcinoma-type testicular carcinoma with metastatic retroperitoneal involvement associated with Wunderlich syndrome 5; In Salgado et al case, the high aggressiveness of this type of testicular tumors is clearly evidenced, documenting metastasis to the kidney and mesentery, confirming with the histopathological result the commitment to choriocarcinoma, patient was treated in intensive care unit for hemorrhagic shock grade IV, acute liver failure and acute renal failure, presenting poor evolution with subsequent death at 24 h [19] . Venkata et al also presented a 23 year old male with increasing abdominal pain, diarrhea, episodic vomiting for 3 weeks, the CT scan of the abdomen revealed a caecal mass with multiple metastases to liver, lungs and abdominal lymph nodes and biopsies from the mass were reported as poorly differentiated metastatic carcinoma.…”
Section: Clinical Discussionmentioning
confidence: 74%
“…In some cases, as in the case of spontaneous retroperitoneal bleeding due to metastatic testicular germ tumor, as reported from Salgado et all, it is not possible to dominate the bleeding just with the embolization. In those cases an exploratory laparotomy with or without partial nephrectomy is needed [12]. A surgical intervention is necessary every time the hypovolemic shock caused by acute bleeding cannot be dominated by arterial embolization.…”
Section: Discussionmentioning
confidence: 99%